Pengembangan media pembelajaran komik pada mata pelajaran IPAS materi Siklus Air kelas V SDN 36 Pontianak Kota - Salsabila, Tira; Basri, Muhammad; Pranata, Rio; Hairida, Hairida; Kresnadi, Hery (UNIB Press, 2025)
The purpose of this study was to determine the validity level of comic learning media in the IPAS subject on the water cycle for fifth grade students at SDN 36 Pontianak Kota. The research method used in this study was research and development (R&D). The development stages in this study used the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The research data used were the results of teacher interviews, student questionnaires, and validation by expert validators. The results of the analysis of the needs of teachers and students showed that comic learning media were needed to support learning activities and that the development of comic media had to be tailored to the characteristics and interests of students in learning. The results showed that the validity of the learning media was based on the assessment of two expert validators, which included aspects of design, material, and language. Based on the validation results for the design aspect, a score of 0.88 was obtained, which is categorized as highly valid. Based on the validation results for the material aspect, a score of 0.98 was obtained, which is categorized as highly valid. Based on the validation results for the language aspect, a score of 0.98 was obtained, which is categorized as highly valid.